2020
DOI: 10.1029/2019gc008795
|View full text |Cite
|
Sign up to set email alerts
|

Silica‐Rich Vein Formation in an Evolving Stress Field, Atlantis Bank Oceanic Core Complex

Abstract: Drilling 809‐m Hole U1473A in the gabbro batholith at the Atlantis Bank Oceanic Core Complex (OCC) found two felsic vein generations: late magmatic fractionates, rich in deuteric water, hosted by oxide gabbros, and anatectic veins associated with dike intrusion and introduction of seawater‐derived volatiles. Microtextures show a change from compressional to tensional stress during vein formation. Temperatures and oxidation state were obtained from amphibole‐plagioclase and oxide pairs in the adjacent gabbros. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 68 publications
(197 reference statements)
0
6
0
Order By: Relevance
“…The first hypothesis implies syn‐tectonic hybridization from a melt rich in H 2 O and incompatible elements. These late‐stage melts are not rare in the oceanic lithosphere, where they crystallize felsic lithologies characterized by amphibole and albitic plagioclase intruded within more primitive gabbros (Basch et al., 2020; Dick et al., 2019; Ma et al., 2020; MacLeod et al., 2017). For instance, Gardner et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The first hypothesis implies syn‐tectonic hybridization from a melt rich in H 2 O and incompatible elements. These late‐stage melts are not rare in the oceanic lithosphere, where they crystallize felsic lithologies characterized by amphibole and albitic plagioclase intruded within more primitive gabbros (Basch et al., 2020; Dick et al., 2019; Ma et al., 2020; MacLeod et al., 2017). For instance, Gardner et al.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Gardner et al (2020) recently showed that the injection of these late-stage melts within a deforming olivine-gabbro in the Atlantis Bank promoted strain localization necessary for nucleation of the oceanic detachment. The origin of melts forming felsic lithologies is debated and include extreme fractional crystallization starting from a basaltic melt (e.g., Nguyen et al, 2018;Basch et al, 2020) or partial melting of preexisting hydrothermally altered gabbros (France et al, 2013;Koepke et al, 2007), or both (Ma et al, 2020). The anomalous composition of the ultra-mylonite could be thus interpreted as resulting from hybridization of a felsic melt localized in the shear zone by crystal plastic deformation.…”
Section: High-temperature Strain Localizationmentioning
confidence: 99%
See 2 more Smart Citations
“…The origin of the different generations of felsic veins appears to be correlated with lower crustal exhumation during emplacement of the OCC. Felsic veins with generally diffuse boundaries, high magnetite/ilmenite ratios and low amphibole Cl/F ratio were interpreted to have formed by fractional crystallization under high-temperature conditions (Nguyen et al, 2018;Ma et al, 2020). Conversely, felsic veins with sharp boundaries and high amphibole Cl/F ratio formed by hydrous melting (anatexis) as a consequence of melt intrusion in hydrothermally altered gabbros (Ma et al, 2020).…”
Section: The Lower Gabbroic Crust In Hole U1473amentioning
confidence: 99%